Students’ Speaking Skills By Using Personal Experience - Razaq, Yusuf; Munawir, Ahmad; Hikmah, Nur; Sriyanti, Sriyanti (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
The main goal of the study was to determine whether or not students in the second year of Boarding School Putra II Sengkang's academic year 2019–2020 can improve their speaking abilities by drawing on personal experience. It was pre-experimental research in this study. The researcher selected VIII.B with 30 students for this study using a cluster random sampling approach. The research's primary tool was a speaking exam. The speaking exam was intended to determine if the second-year students at Boarding School Putra II Sengkang had improved their speaking abilities. The findings of this study show that after treating students with personal experience, their speaking abilities significantly improved. The value (Sig. 2 tailed) was used to demonstrate the point. With a level of significance (α) of 0.05 and a degree of freedom (df) of N-1 = 30, the value (Sig. 2 tailed) is 0.000. The alternative hypothesis (H1) was approved as a result. Based on the findings, the researcher draws the conclusion that the students' speaking abilities were considerably impacted by the application of personal experience, indicating that personal experience helps students talk more clearly.